2007
DOI: 10.1038/sj.npp.1301437
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Abnormal Associations in Schizophrenia: Neural and Behavioral Evidence

Abstract: It is hypothesized that due to an abnormal functioning of the reward system patients with schizophrenia form context-inappropriate associations. It has been shown that the dopamine target regions, especially the ventral striatum, are critical in the formation of reward associations. We wanted to examine how the ventral striatum responds as patients learn reward-related associations and how this neural response is linked to objective and subjective behavioral measures. Functional magnetic resonance imaging (fMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
159
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(184 citation statements)
references
References 35 publications
(54 reference statements)
19
159
1
5
Order By: Relevance
“…Importantly, increased striatal activity during reward anticipation was mostly driven by positive symptoms, which is consistent with our previous study in unmedicated individuals atrisk for psychosis. 19 These findings are in line with studies showing a relation between positive symptoms and increased hemodynamic responses to reward-predicting cues 55 or neutral stimuli in the mesolimbic reward system 21,32,56,57 in individuals at-risk for psychosis and patients with psychotic disorders. In contrast, a recent study in unmedicated patients with schizophrenia has reported a negative association between VS activity during anticipation of wins and losses, ie, salience, with positive symptoms.…”
Section: Discussionsupporting
confidence: 77%
“…Importantly, increased striatal activity during reward anticipation was mostly driven by positive symptoms, which is consistent with our previous study in unmedicated individuals atrisk for psychosis. 19 These findings are in line with studies showing a relation between positive symptoms and increased hemodynamic responses to reward-predicting cues 55 or neutral stimuli in the mesolimbic reward system 21,32,56,57 in individuals at-risk for psychosis and patients with psychotic disorders. In contrast, a recent study in unmedicated patients with schizophrenia has reported a negative association between VS activity during anticipation of wins and losses, ie, salience, with positive symptoms.…”
Section: Discussionsupporting
confidence: 77%
“…Abnormalities in reward processing in schizophrenia can be exacerbated by medication (Schlagenhauf et al 2008), but deficits are also present in patients who are not taking dopamine receptor antagonists (Murray et al 2008b). Furthermore, in schizophrenia, learning about important events is linked with dysfunction in dopaminergic regions such as the striatum and midbrain (Jensen et al 2008 ;Murray et al 2008c). Frontal, temporal and parietal cortical abnormalities are also seen in such processes (Murray et al 2008c, and recent evidence suggests that the degree of abnormality of cortical response is linked to the severity of delusional ideation (Corlett et al 2007 ;Schlagenhauf et al 2009).…”
Section: Influences On Dopamine Neuronsmentioning
confidence: 99%
“…from subclinical to clinical psychotic expression) [13], linking expression of psychosis at 'brain-level' with 'mind-level' 9 . The hypothesized role of aberrant salience as the driving force behind psychotic symptoms has been supported by empirical studies showing that psychotic symptoms were associated with aberrant salience in both patients with schizophrenia and controls with increased liability for psychosis [14] and by imaging studies showing that patients with schizophrenia show abnormal neural patterns in response to neutral stimuli [15,16]. Furthermore, support comes from work in psychopharmacology, suggesting that antipsychotic medication attenuates both the level of psychotic symptoms and the level of aberrant salience [12,14].…”
Section: Prospective Within-person Assessment Of Reactive Mental Statmentioning
confidence: 62%